Nucleolar organizer activity and its regulatory mechanisms in drosophila species of the ‘mulleri’ complex and their hybrids - Hermione, E. M. [UNESP]; Bicudo, C. [UNESP] (Firenze University Press, 1981)
The nucleolar organizer activity was studied in the salivary gland cells of Drosophila species from the ‘mulleri’ complex and their hybrids. The association of nucleoli with chromosomes showed that intraspecifically the X chromosome and the microchromosome are involved in the nucleolar synthesis in every case: the first as the main nucleolus organizer and the second apparently as a minor site operating in a low number of cells. Hybrids, however, revealed inter-specific differentiation in the nucleolar activity and its control. In the female progeny from every inter-specific combination nucleolar dominance was a constant feature, but the specific origin of the dominant nucleolar organizer varied among different combinations. In the male hybrids interspecific variation was detected by the occurrence, in some combinations, of an activation of the microchromosome to operate like the main NO, associated with gene amplification. The degree of gene amplification was another feature which varied among those combinations. These findings were discussed in view of the phylogenetic relationships of the species, previously established on the basis of cytological and genetical analysis. © 1981 Taylor & Francis Group, LLC.